1998
DOI: 10.1113/expphysiol.1998.sp004160
|View full text |Cite
|
Sign up to set email alerts
|

Age‐related changes in oxygen and nutrient uptake by hindquarters in newborn pigs during cold‐induced shivering

Abstract: SUMMARYNewborn pigs rely essentially on shivering thermogenesis in the cold. In order to understand the rapid postnatal enhancement of thermogenic capacities in piglets, the oxygen and nutrient uptake of hindquarters was measured in vivo in 1-(n = 6) and 5-day-old (n = 6) animals at thermal neutrality and during cold exposure. The hindquarters were considered to represent a skeletal muscle compartment. Indirect calorimetry and arterio-venous techniques were used. The cold challenge (23°C at 1 day old and 15°C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 31 publications
1
12
0
2
Order By: Relevance
“…As shown previously [12], this is accompanied by a major rise in NEFA plasma levels, and a decline in the respiratory quotient reflecting the increased involvement of lipids as an energy source. This metabolic switch is likely to occur at the muscular level because, in these conditions, skeletal muscle is known to contribute 34-40% to whole-body oxygen consumption [6]. Indeed, we observed a marked increase in total fatty acid oxidation capacities expressed by g tissue wet weight between birth and five-days of life.…”
Section: Skeletal Muscle Fatty Acid Oxidation Capacities Increased Posupporting
confidence: 51%
See 4 more Smart Citations
“…As shown previously [12], this is accompanied by a major rise in NEFA plasma levels, and a decline in the respiratory quotient reflecting the increased involvement of lipids as an energy source. This metabolic switch is likely to occur at the muscular level because, in these conditions, skeletal muscle is known to contribute 34-40% to whole-body oxygen consumption [6]. Indeed, we observed a marked increase in total fatty acid oxidation capacities expressed by g tissue wet weight between birth and five-days of life.…”
Section: Skeletal Muscle Fatty Acid Oxidation Capacities Increased Posupporting
confidence: 51%
“…The cold-induced enhancement of NEFA plasma levels indicates that adequate mobilization of fat stores occurred. In similar cold conditions, we have also shown that, at this age, fatty acid uptake is stimulated in the skeletal muscle [6] thereby increasing fatty acid availability within the muscle cell. This mechanism was probably responsible for the enhancement of fatty acid utilization because very limited changes in fatty acid oxidation were noticed.…”
Section: 2mentioning
confidence: 67%
See 3 more Smart Citations